PEMBERIAN PAKAN BUATAN DENGAN PERSENTASE YANG BERBEDA PADA PERTUMBUHAN IKAN NILA (OREOCHROMIS NILOTICUS LINN) MENGGUNAKAN HAPPA DI KOLAM KECAMATAN MARTAPURA KABUPATEN BANJAR KALIMANTAN SELATAN - Ramadhana, Sri (Chlorophyl, 2022)
Tilapia is a superior variety fish and is the result of crossing several tilapia varieties in several countries in the world. The purpose of this study was to determine the artificial feeding with different proportions on the growth of tilapia reared using happa in the pond. This research was conducted in Martapura sub-district, Banjar district for 2 months using happa. The test fish in this study had an average weight of 25-33 grams with a standard length of 8-10 cm. The maintenance area uses a pool equipped with 9 pieces of happa measuring 1m x1m x1m. The design method used RAL (Completely Randomized Design) with 3 treatments and 3 replications, namely treatment A (percentage of feed 7%), treatment B (percentage of feed 5%) and treatment C (percentage of feed 3%). Parameters observed included relative weight growth, relative standard length growth, condition factors, feed conversion, survival rate, mortality and water quality as supporting data. The results of the Liliefors normality test and the homogeneity of the Barlett variance showed that all data were normally distributed and homogeneous. The results of the analysis of Diversity (Anova) the growth of the average relative weight of individuals (A=409.69%, B=309.33%, C=259.99%), the relative growth of the average standard length of individuals (A= 73.32 ) %, B=50,98%, C=47,37%). Condition factor (A=4.73, B=4.94 and C 4.99), from the condition factor value, it can be said that the fish is fat (value >4). Conversion of food (A=2.30, B=1.90, C=1.18), water quality during rearing were generally still within the tolerance limits or general range so that they could support the life and growth of the test fish until the end of the rearing